Siberia a history of the people - Hartley, Janet M. (Yale University Press, 2014)
Larger in area than the United States and Europe combined, Siberia is a land of extremes, not merely in terms of climate and expanse, but in the many kinds of lives its population has led over the course of four centuries. One of the world's most inhospitable regions is humanized through personal narratives and colorful case studies as ordinary--and extraordinary--everyday life in 'the nothingness' is presented in rich and fascinating detail.